2021
DOI: 10.1016/j.anr.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Korean Version of the Student Evidence-Based Practice Questionnaire (S-EBPQ)

Abstract: Evidence-based practice (EBP) is a key competency that undergraduate nursing students need to learn, as EBP competence is essential for the effective implementation of EBP. However, few studies have comprehensively assessed the aspects of EBP competence using a reliable and valid measure specific to Korean nursing students. This study aimed to translate the Student Evidence-Based Practice Questionnaire (S-EBPQ) into Korean and evaluate its psychometric properties. Methods: The original S-EBPQ was translated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The study's findings are consistent with those of previous studies as it demonstrated the reliability and validity of the translated S-EBPQ-Chinese version [ 16 ], S-EBPQ-Korean version [ 36 ], and untranslated S-EBPQ-English version [ 14 , 35 , 37 ]. The internal consistency of the Arabic version of the S-EBPQ was 0.897 across the entire scale.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study's findings are consistent with those of previous studies as it demonstrated the reliability and validity of the translated S-EBPQ-Chinese version [ 16 ], S-EBPQ-Korean version [ 36 ], and untranslated S-EBPQ-English version [ 14 , 35 , 37 ]. The internal consistency of the Arabic version of the S-EBPQ was 0.897 across the entire scale.…”
Section: Discussionsupporting
confidence: 90%
“…This can be addressed by using robust measures for EBP. The existing measures have been tested on students globally and translated into different languages, such as Chinese and Korean [ 16 , 36 ]. In particular, the EBPQ has been translated and validated in more than 25 languages.…”
Section: Introductionmentioning
confidence: 99%